Reliability of the two new specific wrestling tests: performance, metabolic and cardiac indicators - Markovic, M.; Dopsaj, M.; Kasum, G.; Zaric, I.; Toskic, L. (Archives of Budo, 2017)
Background and Study Aim: Wrestling belongs to the group of multidisciplinary acyclic sports which require well-trained physical, technical, tactical and psychological abilities. Based on the former result analysis, it can be noticed that there is a need for designing tests for evaluation of wrestlers` specific performance abilities. The aim of the research is the reliability and usefulness quantitative descriptive indicators of given properties of wrestler`s bseed on results two innovative specific tests.